IMPLEMENTASI PENDIDIKAN TAUHID DALAM MEMBENTUK KARAKTER SANTRI PONDOK PESANTREN TAHFIDZUL QUR’AN IMAM AN NAWAWI BATAM: Implementasi Pendidikan Tauhid dalam Membentuk Karakter Santri Pondok Pesantren Tahfidzul Qur’an Imam An Nawawi Batam - Muhammad Hambal Shafwan; Muhammad Mahdi Abdullah (STAI Muhammadiyah Paciran Lamongan, 2024)
This research is motivated by the problem of character crisis faced by the younger generation today. The formulation of the research problems are: (1) What is the character of the new students at Tahfidzul Quran Imam An-Nawawi Islamic Boarding School Batam?; (2) How is monotheism education at Tahfidzul Quran Imam An-Nawawi Islamic Boarding School Batam?; (3) What is the role of tauhid education at Tahfidzul Quran Imam An-Nawawi Islamic Boarding School in Batam in building the character of the students? This research is a qualitative research with a case study type. The results showed: (1) Tahfidzul Quran Imam An Nawawi Islamic Boarding School Batam is a boarding school that makes monotheism education the basis for building the character of students. Because, from the concept of monotheism, a very important standard will emerge in the concept of Islamic education, namely moral standards (value standards) whose essence is good and bad and right and wrong; (2) Tauhid education at Tahfidzul Quran Islamic Boarding School Imam An Nawawi Batam combines learning in the classroom and learning halaqah in the mosque; (3) Monotheism education in the classroom provides a broad and deep understanding of monotheism, while monotheism education through the halaqah method at the mosque is very useful in building the character of the students, including: (a) Educating the students independently; (b) There is closeness between teachers and students; (c) Effective in cultivating ukhuwah Islamiyah; (d) The blessing of knowledge because halaqah is done in the mosque.